Adsorption of various ions from acetone and ethanol on silica gel modified with 2-, 3-, and 4-aminobenzoate - Menezes, M. L.; Moreira, J. C.; Campos, J. T. S. (Elsevier, 1996)
Chemically bonded phases were obtained by reaction of 2-, 3-, and 4-aminobenzoate with 3-chloropropyl-silica gel. These phases were employed for metal cation adsorption in a batch method and applied to the separation of transition metal cations by chromatographic analysis.
Keywords: adsorption; aminobenzoate; cations; separation; acetone; alcohol; aminobenzoic acid; silicon dioxide; chromatography; physical chemistry; priority journal